2000
DOI: 10.1007/s100720070087
|View full text |Cite
|
Sign up to set email alerts
|

Cavernous angiomas of the nervous system in Italy: clinical and genetic study

Abstract: We performed a clinical and genetic study of patients affected by cavernous angiomas (CA) of the nervous system. We examined initial signs and symptoms in sporadic and familial cases. We obtained clinical, neuroimaging and genetic data on 15 Italian patients with CA of the nervous system with positive, doubtful or apparently negative family history. Genetic markers surrounding three different gene regions (7q, 3q and 7p) were analysed. In one small family, genetic linkage was consistent with all chromosome loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2003
2003
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 17 publications
0
6
0
1
Order By: Relevance
“…All of these probands were positively diagnosed with CCMs by magnetic resonance imaging (MRI) and had multiple lesions and/or at least one other family member with a CCM lesion confirmed by MRI. These criteria have been used by us (Sahoo, et al, 1999;Liquori, et al, 2003) and others (Craig, et al, 1998;Squitieri, et al, 2000;Denier, et al, 2004;Bergametti, et al, 2005) as strong indicators of the inherited form of CCM. Significantly, sequence analysis of the CCM1 and CCM2 genes in these probands revealed no mutations.…”
Section: Resultsmentioning
confidence: 99%
“…All of these probands were positively diagnosed with CCMs by magnetic resonance imaging (MRI) and had multiple lesions and/or at least one other family member with a CCM lesion confirmed by MRI. These criteria have been used by us (Sahoo, et al, 1999;Liquori, et al, 2003) and others (Craig, et al, 1998;Squitieri, et al, 2000;Denier, et al, 2004;Bergametti, et al, 2005) as strong indicators of the inherited form of CCM. Significantly, sequence analysis of the CCM1 and CCM2 genes in these probands revealed no mutations.…”
Section: Resultsmentioning
confidence: 99%
“…Four of the families harboring MGC4607 mutations were previously reported as consistent with showing linkage to CCM2 (Craig et al 1998;Squitieri et al 2000;Dupre et al 2003). The remaining five families with…”
Section: Figurementioning
confidence: 86%
“…Three gene loci have already been described, and a fourth locus was recently suspected [Liquori et al, 2006; Plummer et al, 2005]. Although virtually all cases of inherited CCM1 among the Hispanic population of Mexican descent in the United States arise from a founder mutation [Gunel et al, 1996], various CCM1 gene mutations have been reported in the Italian population [Laberge‐le Couteulx et al, 1999; Squitieri et al, 2000; Marini et al, 2003]. The genetic heterogeneity and penetrance variability [Denier et al, 2004] is complicated even further by evidence of Italian families carrying mutations in the other CCM genes, namely the CCM2 gene and a new, under‐study, CCM‐locus [Liquori et al, 2003, 2006].…”
Section: Clinical and Genetic Screening Of Italian Ccm Familiesmentioning
confidence: 99%
“…The genetic heterogeneity and penetrance variability [Denier et al, 2004] is complicated even further by evidence of Italian families carrying mutations in the other CCM genes, namely the CCM2 gene and a new, under‐study, CCM‐locus [Liquori et al, 2003, 2006]. We have set up a clinical and genomic data bank for Italian families with CCMs [Squitieri et al, 2000] and have undertaken comprehensive genetic screening of CCM genes (Table I). Data obtained from the genetic screening highlighted the presence of novel, as yet undescribed mutations, in CCM1 and CCM2 loci in two families, whereas complete sequencing of the CCM3 gene locus detected no mutations in our families.…”
Section: Clinical and Genetic Screening Of Italian Ccm Familiesmentioning
confidence: 99%